Assessment of Solid Waste Management Practices in Kabowohe Division, Sheema Muinicipal Council, Sheema District - Hilda, Karungi (Kabale University, 2023)
Solid waste management is one of the major environmental problems facing municipalities today. Kabwohe Division, Sheema Municipality, like other urban centers in Uganda and in most other developing countries, this important service is based on the city's centralized collection, transportation, and disposal strategy. Currently, this approach has proven to be inefficient due to the heavy financial requirements involved.